Reflectance spectroscopy as a tool for settled dust monitoring in office environment. (29th June 2009) - Chudnovsky, Alexandra; Ben-Dor, Eyal
The aim of this study was to develop a technique based on reflectance spectroscopy that is capable of evaluating small amounts of sediment dust. Laboratory simulations and two field experiments conducted in the same office environment were carried out to generate particulate dust samples based on multivariate data analyses. Spectral measurements were taken using either a laboratory Quantum 1200 (1200-2400 nm) or a field ASD (350-2500 nm) spectrometer separately provided spectra that could be used to generate accurate predictions of gravimetric weight, with the relatively low Root Mean Square Error of Prediction (%RMSEP) ranging from 6% to 11.5%.